SOME PHYTOCHEMICAL CONTENTS AND ANTIOXIDANT ACTIVITIES OF TWO PRANGOS LINDL. (UMBELLIFERA) SPECIES GROWN IN TURKEY - Hayta, Sukru; Aydin, Sevinc; Topdemir, Aykut (Pakistan Botanical Soc, 2022)
The genus Prangos is a member of the Apiaceae family, and it has been a focus of the attention of researchers due to its high nutritional value and some special medical properties. In this study, the total phenolic and flavonoid contents and antioxidant activities of the leaf and fruit extracts of the Prangos ferulacea and Prangos uloptera species belonging to this genus were studied, and the properties of these two species were compared to each other. In the study, the Folin-Ciocalteu method was used for the analysis of the total phenolic content, methanolic formaldehyde was used for the total flavonoid content, and both analyses were carried out with a UV-VIS spectrophotometer device. The antioxidant activity of the specimens was measured based on the Trolox equivalent antioxidant capacity (TEAC) method. It was found that the P. ferulacea species had higher total phenolic and flavonoid content values than the P. uloptera species. The P. ferulacea species was also more effective in terms of antioxidant activity, which is known to be associated with these properties. When the fruit and leaf extracts of each species were compared, it was found that the total phenolic and flavonoid content of the fruit extract of the P. uloptera species was higher than that of its leaf extract, and the antioxidant activity of the fruit extract was also higher in proportion to these values. In the P. ferulacea species, as opposed to the case of P. uloptera, all values except for the total flavonoid values were higher in the leaf extract than the fruit extract.
Keywords: Prangos ferulacea; Prangos uloptera; Total flavonoid; Total phenolic